Properties of Gaussian Beam Propagating in Ring Resonator Sensor - Long Jin; Zhiqiang Yang; Qiang Zhang (International Journal of Optics)
In this paper, we deduce the paraxial analytical expression for the Gaussian beam propagating in the sandwich slab system which contained double negative material based on light transfer matrix and generalized Huygens-Fresnel integral equation; the evolution properties of emerging Gaussian beam contour graph intensity distribution on the receiver plane, the relation between beam spot size and negative refractive index coefficient, and beam side transmission view in slab system changed with three negative refractive index parameters are illustrated through numerical examples. What is more, we propose a ring resonator sensor to measure the concentration of NaCl solution on the basis of above theory, of which the operating principle is deliberatively analyzed, the influence of the concave mirror curvature radius on the emerging beam evolution is acquired, the functional relation between the normalized central intensity of the emerging beam, the beam spot size, and NaCl solution concentration is further developed by fit linear method, and the mathematical statistics results reach high precision and linearity. It is expected that the proposed ring resonator sensor and the corresponding conclusions can be useful for precise optical measurement, especially for food safety inspection and medical services of health care.